Tracing Smart Cities’ Representation on Twitter. An Analysis of the Italian Context - Calicchia, Francesco; Capuano, Maria Elena; Iazzetta, Ferdinando (Italian Sociological Review, 2024)
In recent years, various disciplines have focused on the Smart City concept and phenomenon. Whether people can approach the smart city concept without fear and risk of losing their sensitive data is still a major concern. This paper intends to investigate, through an analysis conducted by extrapolating tweets on the social media Twitter, the relationship existing between the Smart City and Italian citizens. The objective consists in a descriptive content analysis capable of providing a perception and use of the Smart City concept relative to the Italian population.